Pengaruh Earning Per Share (EPS) dan Pertumbuhan Penjualan Terhadap Harga Saham Pada Perusahaan Tekstil dan Garmen di BEI - Fortiwa Situmorang; M Khoiri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
tock prices in Textile and Garment companies listed on the IDX from 2017-2021. The purpose of these 7 sales is to see whether earnings per share, growth, price of shares that have been listed on the Indonesia Stock Exchange from 2017 to 2021. The number of samples in this study are textile and garment companies listed on the Indonesia Stock Exchange. Purposive sampling method in this study was used to determine the sample. The data technique used multiple linear regression analysis with the help of SPSS version 26. This review resulted in earnings per share having no significant effect on stock prices, indicated by a value of 0.419 > 0.05. The sales growth indicator does not have a significant effect on stock prices in textile and garment companies listed on the IDX for the 2017-2021 period with a significant value of 0.321 > 0.05. Simultaneously, earnings per share and sales growth affect the stock prices listed on the IDX for the 2017-2021 period